2007
DOI: 10.1038/nprot.2007.251
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for isolation and visualization of yeast nuclei by scanning electron microscopy (SEM)

Abstract: This protocol details methods for the isolation of yeast nuclei from budding yeast (Saccharomyces cerevisiae) and fission yeast (Schizosaccharomyces pombe), immuno-gold labeling of proteins and visualization by field emission scanning electron microscopy (FESEM). This involves the removal of the yeast cell wall and isolation of the nucleus from within, followed by subsequent processing for high-resolution microscopy. The nuclear isolation step can be performed in two ways: enzymatic treatment of yeast cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…, 1998; Kiseleva et al. , 2004, 2007). Crucially, our IEM studies indicate that Mlps not only form the basket at the NPC, but are also arranged horizontally along the plane of the NE and are found in areas bridging neighboring nuclear pores (also see Strambio-de-Castillia et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 1998; Kiseleva et al. , 2004, 2007). Crucially, our IEM studies indicate that Mlps not only form the basket at the NPC, but are also arranged horizontally along the plane of the NE and are found in areas bridging neighboring nuclear pores (also see Strambio-de-Castillia et al.…”
Section: Discussionmentioning
confidence: 99%
“…Replication factories were isolated using the spheroplast methodology [39,40]. Specifically, Acanthamoeba polyphaga were cultivated and infected by Mimivirus.…”
Section: Methodsmentioning
confidence: 99%
“…Electron microscopic studies revealed that the NPC is a cylindrical structure consisting of a central core with an 8-fold rotational symmetry across a nucleocytoplasmic axis and a 2-fold symmetry in the plane of the nuclear envelope (5)(6)(7)(8). This symmetric core is linked to the asymmetric cytoplasmic filaments and a nuclear basket structure (9).…”
mentioning
confidence: 99%